2015
DOI: 10.1080/13102818.2015.1105726
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of autochthonous grapevine cultivars from Eastern Turkey by simple sequence repeats (SSRs)

Abstract: In this research, two well-recognized standard grape cultivars, Cabernet Sauvignon and Merlot, together with eight historical autochthonous grapevine cultivars from Eastern Anatolia in Turkey, were genetically characterized by using 12 pairs of simple sequence repeat (SSR) primers in order to evaluate their genetic diversity and relatedness. All of the used SSR primers produced successful amplifications and revealed DNA polymorphisms, which were subsequently utilized to evaluate the genetic relatedness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…There were 1-8, 1-8 and 1-7 alleles per locus of each group identified from the used 15 pairs SSR markers, which was consistent with the previously reported data of 4-16 alleles per locus in V. vinifera germplasms [3,9,12,24,25]. The average number of 3.6, 4.4 and 3.6 alleles per locus was a little lower than in contrast earlier reports of 10 autochthonous cultivars (5.75) from Eastern Turkey [4], 25 autochthonous cultivars (8.67) from northeastern Turkey [26], 33 Slovenian cultivars (8.00) [27], 11 Romanian cultivars (7.90) [28], 50 Greek cultivars (7.90) [29] and 51 accessions from Bosnia and Herzegovina (7.82) [30]. The reason may be that the groups we had chosen were small, the varieties were few in each population, and all the cultivars in each group had similar traits.…”
Section: Primersupporting
confidence: 91%
See 3 more Smart Citations
“…There were 1-8, 1-8 and 1-7 alleles per locus of each group identified from the used 15 pairs SSR markers, which was consistent with the previously reported data of 4-16 alleles per locus in V. vinifera germplasms [3,9,12,24,25]. The average number of 3.6, 4.4 and 3.6 alleles per locus was a little lower than in contrast earlier reports of 10 autochthonous cultivars (5.75) from Eastern Turkey [4], 25 autochthonous cultivars (8.67) from northeastern Turkey [26], 33 Slovenian cultivars (8.00) [27], 11 Romanian cultivars (7.90) [28], 50 Greek cultivars (7.90) [29] and 51 accessions from Bosnia and Herzegovina (7.82) [30]. The reason may be that the groups we had chosen were small, the varieties were few in each population, and all the cultivars in each group had similar traits.…”
Section: Primersupporting
confidence: 91%
“…Genomic DNA was extracted from young leaf tissues by the method of Thomas and Scott [4] with minor modifications. DNA integrity was confirmed using 1% (w/v) agarose gel electrophoresis, and DNA concentration and purity were determined by Bio-Photometer (Eppendorf BioSpectrometer Germany).…”
Section: Genomic Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…A relatively low rate of nucleotide variation in a-TPS was observed in the grapevine varieties considered. The frequency of SNPs in the a-TPS coding region found in study was slightly lower than that reported in other grapevine studies, wherein a frequency of one SNP per 47-64 bp was detected on average [28][29][30][31][32]. This might be due to differences in the sample size and uneven distribution of polymorphisms in the grapevine genome.…”
Section: A-tps Nucleotide Diversitycontrasting
confidence: 83%